NIMS fatigue data sheet on gigacycle fatigue properties of Scr420 (0.20C-1.05Cr) carburizing steel for machine structural use. Issue 1 (31st December 2022) - Hirukawa, Hisashi; Furuya, Yoshiyuki; Nishikawa, Hideaki; Nagashima, Nobuo; Takeuchi, Etsuo
ABSTRACT: The new fatigue data sheet, No. 131, discloses gigacycle fatigue properties of the carburizing steel tested under rotating-bending conditions. This fatigue data sheet employed vacuum carburizing, as well as gas carburizing. Both as carburized and polished specimens were tested. In case of the polished specimens, two conditions of hardened layer depths were applied, i.e. deep and shallow cases. The fatigue test results demonstrated that gigacycle fatigue took place in the carburizing steel. Many specimens failed at over 10 7 cycles, ending in internal fractures. The origins of the internal fractures were oxide-type inclusions located in or beneath the hardened layer. The as carburized specimens of the vacuum carburizing revealed higher fatigue strength than those of the gas carburizing. One of the reasons of this improvement was fine microstructures created by the vacuum carburizing at around the surfaces. The polished specimens showed further high fatigue strength, developing more internal fractures. The deep case then revealed higher fatigue strength than the shallow case. In case of surface fractures, typical fatigue fracture surfaces were not observed, i.e. only intergranular fracture surfaces were observed in the hardened layers. Fish-eye patterns were observed in case of the internal fractures, while outsides of the fish-eye patterns were the intergranular fracture surfaces. Our interpretation was that the hardened layers were too brittle to allow conventional fatigue crack growth. In other word, the hardened layers were brittle-fractured immediately after the crack initiation, or only internal fatigue crack growth were allowed. Graphical abstract: uf0001